Inovação e competitividade em segmentos potencialmente exportadores: o caso da aglomeração de instrumentos, médico-odonto-hospitalares de Curitiba - Holler, Carla (2009)
Many enterprises have been trying to achieve a competitive advantage in order to be able to remain in the market. One of the ways encountered by these companies is to associate with other companies of the same type in order to be able to face some difficulties/trouble. There are several concepts to name these joints. The complex clusters in on of the names for the different kinds of enterprise gathering. Is definition is based on the fact that the enterprises which gather/join with others are able to export their products more easily. They represent important arrangements for an accelerate and efficient technological development advantage, considering the creation of competitive advantage through the continuers learning with international business. In Brazil, Arranjo produtivo Local – APL (Local Productive Arrangement) is the most used terminology for this kind of gathering. More specifically, this study has been done in the gathering of medical-dental-hospital tools, equipment and appliances of Curitiba. In this context, innovation has been given a role of distinction for achieving competitive differentials by the associations. Is a consequence, these gatherings have a competitive advantage if compared to their competitors. This research started with studies done by Instituto Paranaense de Desenvolvimento Econômico e Social – IPARDES, was identified as an APL. In this research, the exportation potential was approached, which is a central concept developed by Wixted (2006) as a complex cluster. Besides that, the basis for choosing this gathering was the fact that some of these enterprises are on the international market and their products have a high standard technology. For this reason, the present paper analyses the way in which the innovation, performed, done, by the companies located in the clusters of enterprises influenced their competitive advantages. The analysis focus is the relation between complex clusters, innovations and competitive advantages. The methodological approach of the research was a qualitative kind, classified as exploratory, looking at the study of the case as a method of procedure. In order to collect the data, semi-structured interviews were done with the managers/heads of four enterprises belonging to the of medical-dental-hospital tools, equipment and appliances of Curitiba. Two of these companies deal with export, third one is in the process of starting to export and the fourth company has not been in the export business so far. The results suggest that the enterprises have been benefited by the innovations, being able to increase their sales and profit, as well entering new markets and launching new products. Nevertheless, the competitiveness occurs only due to innovation, not to cooperation or belonging to a specific type of gathering. The result also shows that the enterprises that were on the research innovate their products more frequently. Also, the canals of information flow refer, basically to taking part in fairs, national and international seminars, access to specialized magazines or publishing, as well as meetings of businesses of the same activity.